P060 Unravelling the microbial-derived metabolic alterations in a T-bet-/- x RAG2-/- mouse colitis model. (21st January 2022) - Liu, Z; Lo, J; Alexander, J; Cozzetto, D; Powell, N
Abstract: Background: T-bet ( Tbx21 ) is a T-box transcription factor that can regulate immune cells' differentiation and function. Loss of T-bet leads to the absence of adaptive immunity. T-bet -/- x RAG2 -/- mice develop spontaneous ulcerative colitis (TRUC) that resembles human colitis, thus they are widely used as a colitis model in recent years. While many researchers studied the host and gut microbiota interaction in immune dysregulation, how the host and bacteria metabolites regulate the immune response is less understood. Methods: TRUC and Rag2 -/- (as a control group) mice models were employed. When TRUC mice developed anorectal prolapse and rectal inflammation, mice colon tissue and faeces were collected for gene expression analysis and metabolic profiling, respectively. Metabolites were measured by Nuclear Magnetic Resonance and Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) was performed to determine differential metabolites. Metabolite enrichment analysis was done using MetaboAnalyst. RNA-seq was employed for colon gene expression. Differential genes were generated with DESeq2 package and enrichment analysis was conducted with clusterProfiler package. Results: Principle component analysis of the metabolic profile showed a clear separation between Rag2 -/- and TRUC group (Fig 1A). The OPLS-DA model between the two groups is robust (R 2 = 0.55, Q 2 = 0.89, p-value = 0.03). 12 metabolites were significantly changed. Alanine, butyrate, beta-glucose, glycerol, lysine, pyruvate, gamma-aminobutyrate, dimethylamine, galactose, hypoxanthine and aspartate were significantly increased in TRUC mice compared to Rag2 -/- mice, while tyramine was decreased (Fig 1B&C). Metabolite enrichment analysis showed that glycolysis, glucose-alanine cycle, gluconeogenesis, etc. were among the most enriched pathways (Fig 1D). KEGG module over-representation analysis also identified these glucose-related metabolic pathways as top enriched pathways with many genes increased in TRUC mice (Fig 2). In addition to metabolic pathway perturbance, gene set enrichment analysis suggested that cytokine production and regulation were notably altered in TRUC mice, as well as the response to molecules of bacterial origin (Fig 3). Conclusion: TRUC mice with ulcerative colitis have significantly affected gut-host metabolism. The up-regulation of glucose-related metabolic pathways suggested increased energy consumption. Increase of butyrate, dimethylamine and enriched genes in response to bacteria implied the host-bacteria interaction process. Further investigation of gut microbiota alteration and integration of bacteria-metabolites-host immune response axis is warranted to determine whether targeting certain pathways can be harnessed as a novel therapy to colitis.